Scheduling with deterioration effects and maintenance activities under parallel processors. Issue 12 (2nd December 2021) - He, Hongyu; Hu, Yang; Liu, Wei-Wei
ABSTRACT: This article considers unrelated parallel processor scheduling problems with deterioration effects and processor maintenance activities. In this case, deterioration occurs during processing. A maintenance activity on a parallel processor is allowed after a job is processed, and the maintenance time is a fixed constant. After the maintenance work is completed, the processor is restored to the initial state, and job deterioration starts again. The goal of this article is to determine the location of the processor maintenance activity and to find the optimal sequence to minimize the total completion time and total machine load. It is shown in this article that these problems are polynomial-time solvable and the corresponding algorithms are provided.